Evidence of Differential Effects of Vitamin D Receptor Variants on Epithelial Ovarian Cancer Risk by Predicted Vitamin D Status - Prescott, Jennifer; Bertrand, Kimberly A.; Reid, Brett M.; Permuth-Wey, Jennifer; De Vivo, Immaculata; Cramer, Daniel W.; Terry, Kathryn L.; Tworoger, Shelley S. (Frontiers in Oncology, 2014)
Introduction: Experimental studies suggest vitamin D inhibits ovarian carcinogenesis. Yet, epidemiologic studies of ovarian cancer risk and lifestyle correlates of vitamin D status, plasma 25-hydroxyvitamin D [25(OH)D], or vitamin D receptor (VDR) variants have been inconsistent. Objective: To evaluate VDR genetic associations by high vs. low predicted 25(OH)D, scores derived from known determinants of plasma 25(OH)D. To assess ovarian cancer associations with variants identified in genome-wide association studies (GWAS) of plasma 25(OH)D. Methods: We genotyped up to seven VDR and eight 25(OH)D GWAS variants in the Nurses’ Health Studies (562 cases, 1,553 controls) and New England Case–Control study (1,821 cases, 1,870 controls). We estimated haplotype scores using expectation-maximization-based algorithms. We used unconditional logistic regression to calculate odds ratios (ORs) and 95% confidence intervals (CI). We combined study results using DerSimonian and Laird meta-analysis. Results: Ovarian cancer risk increased per A allele of rs7975232 (VDR; OR = 1.12, 95% CI = 1.01–1.25) among all women. When stratified by predicted 25(OH)D, ovarian cancer was associated with rs731236 (VDR; per C allele OR = 1.31) and rs7975232 (OR = 1.38) among women with high predicted 25(OH)D, but not among women with low levels (P ≤ 0.009). We also observed heterogeneity by predicted 25(OH)D for the ovarian cancer association with VDR 3′ end haplotypes (P = 0.009). Of 25(OH)D-associated GWAS loci, rs7041 was associated with reduced ovarian cancer risk (per T allele OR = 0.92, 95% CI = 0.85-0.99), which did not differ by predicted 25(OH)D status. Conclusion: Our study suggests an influence of VDR 3′ end variants on ovarian cancer risk may be observed in women with high predicted 25(OH)D, which remained even after taking multiple comparisons into consideration. Future studies are needed to confirm our results and explore further the relation between vitamin D exposure, genetic variants, and ovarian cancer risk.